Analisis Hasil Implementasi Pengembangan Aplikasi Mobile Pendekatan Hybrid Pada Aplikasi Family Tracking - Miftachul Huda; Indah Lestari; Anggy Trisnadoli (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Family Tracking is a mobile application that utilizes GPS technology to find out the location of each family member. There are several features such as the activity schedule, group chat, and the supervision area added by parents to the child's activity schedule. This application was developed with hybrid approach using Ionic 3 Framework development tools with support of Firebase backend. With the hybrid approach can produce multi-platform applications using the same source code. In this research the application was developed for the Android and iOS platforms. Based on functionality testing in accordance with ISO 9126-2 standards, that all features and functions contained in the application run well on both platforms. Then based on the application performance testing on each device that has the same benchmark value, the application can run stablen iOS devices but has the highest memory usage compared to Android devices with an average difference of 33.81mb. And then applications on iOS devices have lower CPU usage than Android devices, with differences in usage averaging 18.79%. Then based on the results of interviews to get user feedback, the results show that the application can running well and function as expected on Android and iOS devices.